Benefits of Contrast-Enhanced Ultrasonography to the Differential Diagnosis of TI-RADS 4-5 Thyroid Nodules - Ping Yu; Sihua Niu; Shuang Gao; Hui Tian; Jiaan Zhu (Applied Bionics and Biomechanics, 2022)
Objective. The early detection, diagnosis, and treatment of thyroid cancer are of great significance to the prognosis for patients. This study was aimed at exploring the benefits of contrast-enhanced ultrasonography (CEUS) to the differential diagnosis of thyroid nodules classified as TI-RADS class 4 or 5. Method. A total of 46 patients with TI-RADS 4-5 thyroid nodules admitted in Peking University People’s Hospital from January 2019 to January 2021 were selected to study. The sensitivity, specificity, accuracy, and positive and negative predictive values of conventional ultrasonography (US) and conventional ultrasonography combined with contrast-enhanced ultrasonography (US + CEUS) in the diagnosis of benign and malignant thyroid nodules were compared by referring to the results of the surgical pathology report, which is seen as the “gold standard” for diagnosis, followed by the construction of receiver operating characteristic curves (ROCs). Result. Among 57 thyroid nodules, there were statistically significant differences between benign and malignant thyroid nodules in terms of echogenicity, margin characteristics, aspect ratio, and calcification (P<0.01). In the case of CEUS, there was no statistically significant difference among contrast agent perfusion patterns in distinguishing between benign and malignant thyroid nodules (P>0.05). However, there were statistically significant differences among different enhancement degrees, enhanced borders, and enhancement patterns. By comparing the CEUS results of TI-RADS 4-5 thyroid nodules with the results of pathology report, the malignancy rate was found to pathology report results, the malignancy rate was 53.85% in TI-RADS class 4 thyroid nodules and 100.00% in TI-RADS class 5 thyroid nodules. Among thyroid nodules diagnosed using US, 6 benign nodules were misdiagnosed as malignant and 7 malignant nodules were misdiagnosed as benign. Among those diagnosed using US + CEUS, 2 benign nodules were misdiagnosed as malignant and 2 malignant nodules were misdiagnosed as benign. The sensitivity, specificity, accuracy, positive predictive value, and negative predictive value of UN + CEUS significantly outperformed those of UN alone in diagnosing thyroid nodules (P<0.05). The ROC curve analysis showed that the area under the curve (AUC) derived from US + CEUS was 0.849, while the AUC from US was only 0.726. Conclusion. Using US + CEUS to diagnose thyroid nodules classified as TI-RADS category 4 or 5 can further improve distinguishing between benign and malignant nodules. The CEUS is of important value to clinical applications as it can provide effective supplementary information and quantitative analysis for the differentiation between benign and malignant thyroid nodules.